Reduction in Rejection Rate of Soy Sauce Packaging via Six Sigma - Ronald Sukwadi; Leonardus Harijanto; M.M. Wahyuni Inderawati; Po Tsang B. Huang (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
The Six Sigma methodology is the most powerful quality improvement technique. This research deals with applying the Six Sigma methodology in reducing the rejection rate of soy sauce packaging in food production. The DMAIC methodology of Six Sigma provides a step-by-step quality improvement methodology in which statistical techniques are applied. The leakage and cutting error problems were identified in the Define phase. The extent of the problem was measured in the Measure phase. The current DPMO value was 5,794.39, and the sigma level at 4.0245. The root cause of the problem and the improvement priority were identified in the Analyze phase by applying the fishbone diagram and FMEA. The design of new Standard Operating Procedures (SOPs) and preventive maintenance schedule were used in the Improve phase to increase the sigma level by 50-60 percent and decrease DPMO by 99 percent for the upcoming four months implementation. Furthermore, a control plan was provided in the Control phase to monitor and sustain the achieved improvements.